"Going niche" for ASEAN economic community - Pitakdumrongkit, Kaewkamol (2014)
ASEAN governments are having difficulty implementing 20 percent of the AEC Blueprint because of domestic constraints. However, the protectionist forces can be lessened to advance AEC by a strategy of niche production.